Studi Komparasi Perencanaan Ruang Terbuka Hijau Perkotaan Antara Jakarta dan Singapura - Retno Setiowati; Hayati Sari Hasibuan; Raldi Hendro TS Koestoer (Jurnal Lanskap Indonesia, 2020)
Green open space has functions ecologically, economically, and socially to improve the quality of urban life. Urban green space is one of the keys to sustainability. The purpose of this study was to analyze green open space planning in Jakarta and Singapore using a comparative study method. The study locations were chosen in Jakarta and Singapore because they are geographically located in Southeast Asia but have a vastly different area of ​​green open space. Singapore has the largest area of ​​green open space in the world, amounting to 47% of the total area and Jakarta only has a range of 5 to 10% because of the baseline of green open space that has not been officially set by the Government. Green open space planning in Jakarta has decreased from 1965 to the present due to the rapid development of residential and commercial areas. On the other hand, Singapore's success in increasing the area of ​​green space is due to its strong political policy in greening which is directly led by the Prime Minister and supported by all stakeholders. The vision of Singapore as a Garden City is clearly stated in the Green and Blue Master Plan and implemented in government programs. Cooperation between stakeholders in Singapore continues to make public awareness about successful greening. Jakarta needs a strong political policy to increase green open space by formulating a green open space Master Plan that is integrated with a network of roads, blue spaces, and increased cooperation between stakeholders.